The Effectiveness of Augmented Reality Book to Improve Critical Thinking Ability At Elementary School Students - Sukasih, Sri; Wulandari, Desi; Permana, Zahnara Fiki (Journal of Education for Sustainability and Diversity, 2022)
A good learning process is learning that utilizes innovative learning media to help students understand the material and develop critical thinking skills. Critical thinking is an ability that can be learned and trained in order to be able to solve problems effectively. Developing critical thinking skills through technology-based learning media, namely Augmented Reality. Augmented Reality is an application that combines the real world with the virtual world in two-dimensional and three-dimensional forms that are projected in a natural environment at the same time. Augmented Reality Book (ARB) is one of the developments of technology-based learning media that can be applied through Android. Based on these problems, the purpose of this study was to determine the level of effectiveness of ARBs. The data collection method used a questionnaire with a purposive sampling technique. The results obtained include student and teacher responses regarding ARB. ARB is more effective for developing students' critical thinking skills with t table19.426 with a significance level of 0.5%. The results of the t-test show that t_0 is 19.426, and the results of the N-gain analysis show a value of 0.55813. It can be concluded that there is an increase in the average score of students significantly in the moderate category.